Environmental Law: A Perspective on Harmonizing Waste Management Regulations: I Gusti Ayu Putri Kartika (Focus Journal : Law Review, 2026)
The increasing volume of waste generated by households/industries (upstream) and the increasing population density from year to year, in this case, the increasing population in each region, has led to an increase in the amount of waste generated by households/industries. Therefore, a revision of Government Regulation Number 81 of 2012 concerning the Management of Household Waste and Household-Like Waste is crucial. The purpose of this study is to provide a model for reviewing the revision of Government Regulation Number 81 of 2012 concerning the Management of Household Waste and Household-Like Waste, by harmonizing Government Regulation Number 81 of 2012 with the provisions of Law Number 32 of 2009 concerning Environmental Protection and Management, to avoid normative conflicts in the application of waste management regulations. The research method used is a normative juridical research method, implemented through a statutory regulatory approach, a literature review, and a comparative legal approach to obtain research results. The research findings demonstrate the importance of revising Government Regulation No. 81 of 2012 concerning the Management of Household Waste and Household-Like Waste. This is necessary because Law No. 32 of 2009 concerning Environmental Protection and Management and Law No. 18 of 2008 concerning Waste Management emphasize criminal penalties for improperly managed Final Disposal Sites (TPA) that pollute the environment. However, Government Regulation No. 81 of 2012 concerning Waste Management focuses more on administrative technicalities (transportation/disposal) than on criminal acts of pollution, creating ambiguity in the application of criminal articles specifically related to environmental pollution.